Implementation of Clean and Healthy Lifestyle Behavior in Elementary School Students - Rizqy Aiddha Yuniawati; Inggil Wirya Pranata; Nala Auna Robbika; Galih Haryo Permadi; Mochamad Nuril Anwar; Rachel Ariela Davy Eka Putri; Hikma Urwatil Wusqo; Sausan Syahira Arsyie; Nisrin Novel; Sylvi Maria Fransisca (Jurnal Pengabdian Masyarakat Bestari, 2023)
On July 20 2022, Community Service was held in the village of Kemuningsari Kidul, Jenggawah, Jember. To prevent various diseases, this community service aims to provide knowledge, understanding, and skills on how to live a clean and healthy life, especially for children in elementary schools. In this activity, students were given material on washing hands with running water and soap. This activity was continued with the best poster competition, where students were given masks and sanitizers. In this community service, site surveys, problem finding, outreach, provision of facilities, and evaluations are carried out. After evaluation, it can be interpreted that this activity can improve the understanding and skills of Kemuningsari Kidul 01 Elementary School students regarding Clean and Healthy Behavior.